2021
DOI: 10.1530/ec-20-0555
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-reoxygenation treatment attenuates gestational diabetes mellitus

Abstract: Background: Oxidative stress leads to insulin resistance and gestational diabetes mellitus (GDM). The nuclear factor erythroid 2-related factor 2 (Nrf2) / heme oxygenase-1 (HO-1) signaling is an important anti-oxidative stress pathway, which can be activated by hypoxia‑reoxygenation (H/R) treatment. We aimed to demonstrate the effects of H/R treatment on GDM symptoms as well as reproductive outcomes. Methods: Pregnant C57BL/KsJ db/+ mice were used as a genetic GDM model. Plasma insulin and other biochemical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It has been shown earlier in a diet‐induced IR model that an exercise‐mediated improvement in maternal insulin sensitivity rescued the insulin sensitivity of her male offspring, indicating that hyperinsulinemia is a key programming factor, and therefore an important interventional target, during obese pregnancy (Fernandez‐Twinn et al, 2017 ). Moreover, in a genetic GDM model involving db/+ mice, hypoxia/reoxygenation treatment (1 h 6% O 2 followed by reoxygenation at 21% O 2 once a day), markedly ameliorated β‐cell insufficiency and glucose intolerance, suppressed oxidative stress and stimulated antioxidant enzymes, leading to improved reproductive outcomes (Hou et al, 2021 ). The sustained moderate environmental hypoxia (15% O 2 ) used in the present work significantly improved the glucose tolerance and HOMA‐IR scores of the dams with diet‐induced IR compared with normoxia, even maintaining the levels seen in the NC controls, which could indicate beneficial effects on maternal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown earlier in a diet‐induced IR model that an exercise‐mediated improvement in maternal insulin sensitivity rescued the insulin sensitivity of her male offspring, indicating that hyperinsulinemia is a key programming factor, and therefore an important interventional target, during obese pregnancy (Fernandez‐Twinn et al, 2017 ). Moreover, in a genetic GDM model involving db/+ mice, hypoxia/reoxygenation treatment (1 h 6% O 2 followed by reoxygenation at 21% O 2 once a day), markedly ameliorated β‐cell insufficiency and glucose intolerance, suppressed oxidative stress and stimulated antioxidant enzymes, leading to improved reproductive outcomes (Hou et al, 2021 ). The sustained moderate environmental hypoxia (15% O 2 ) used in the present work significantly improved the glucose tolerance and HOMA‐IR scores of the dams with diet‐induced IR compared with normoxia, even maintaining the levels seen in the NC controls, which could indicate beneficial effects on maternal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In previous investigations, oxidative stress was found to be an essential factor in the development of gestational diabetes. Clinical and experimental investigations showed that different reasons related to hyperglycemia, which leads to ROS formation through various biochemical pathways such as glycation of protein and glucose autoxidation (Hou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important part in the pathophysiology of GDM ( 5 , 23 , 24 , 25 , 26 , 27 ). Nevertheless, it remains unclear whether the SNPs CYBA C242T and MPO G-463A are associated with GDM.…”
Section: Introductionmentioning
confidence: 99%